The Effect of External Conditions on Growth in Latin America - Zettelmeyer, Jeromin (IMF Working Papers; Working Paper, 2007)
This paper investigates the sensitivity of Latin American GDP growth to external developments using a Bayesian VAR model with informative steady-state priors. The model is estimated on quarterly data from 1994 to 2006 on key external and Latin American variables. It finds that 50 to 60 percent of the variation in Latin American GDP growth is accounted for by external shocks. Conditional forecasts for a variety of external scenarios suggest that Latin American growth is robust to moderate declines in commodity prices and U.S. or world growth, but sensitive to more extreme shocks, particularly a combined external slowdown and tightening of world financial conditions.